PENGGUNAAN GAIRAIGO DALAM NOVEL KIMI NO NA WA KARYA MAKOTO SHINKAI - Moch Gilang Pratama; Mohammad Ali (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2021)
The purpose of this study was to determine the type of gairaigo vocabulary used and the reasons for using gairaigo vocabulary in the novel Kimi No Nawa by Makoto Shinkai. The method used is a qualitative descriptive with semantic feature inside semanteme method for data analysis. The data collected in the form of the gairaigo vocabulary in the novel then analyzed by comparing the meanings between the gairaigo, the original vocabulary in English and the equivalent of the gairaigo vocabulary in Japanese. The results showed that the reason for using gairaigo vocabulary in the novel Kimi No Nawa was because gairaigo was more appropriate to describe objects in the novel, then the gairaigo is more in line with the trend of word use in today's society, and the gairaigo has a higher value than its equivalent in Japanese.